Microwave ablation triggers OX40L-mediated disruption of TNFRSF4+ Treg immunosuppressive activity - Guo, Runqi; Wang, Yufeng; Sun, Jie; Li, Yuanming; Bie, Zhixin; Li, Xiaoguang (Frontiers in Immunology, 2025)
ObjectiveRegulatory T cells (Tregs) play a pivotal role in tumor immune evasion, and strategies to overcome their immunosuppressive activity are urgently needed. This study investigates the immunomodulatory effects of microwave ablation (MWA) on TNFRSF4+ Tregs, focusing on the OX40L/TNFRSF4 signaling axis as a potential therapeutic target.MethodsTNFRSF4+ Tregs were isolated from C57BL/6 mice and subjected to MWA-mimetic thermal stress. In vitro functional assays and in vivo LLC xenograft models were employed, with OX40 agonist intervention. Molecular mechanisms were analyzed via RT-qPCR, Western blot, and immunohistochemistry. The balance of tumor-infiltrating immune cells was quantified by multi-color flow cytometry.ResultsMWA induced three key effects: (1) Phenotypic shift: decreased CTLA-4+ (P<0.0001) Treg subsets, but increased OX40L+ (P<0.01) in LLC cells; (2) Functional impairment: reduced Treg-mediated support for LLC proliferation, migration, and invasion; (3) Enhanced CD8+ T cell cytotoxicity. In vivo, MWA reshaped the tumor microenvironment by significantly increasing the intratumoral CD8+/Treg ratio (P<0.001), indicating a shift toward an anti-tumor inflammatory state. Mechanistically, MWA suppressed NF-κB/IκBα/TRAF6 signaling, and these effects were amplified by an OX40 agonist, suggesting the pathway is potentially OX40L-dependent.ConclusionThis study demonstrates that MWA disrupts Treg immunosuppression, likely by activating OX40L/TNFRSF4 signaling, and favorably alters the balance of effector to suppressor cells, providing a novel rationale for combining thermal ablation with OX40-targeted immunotherapies in cancer treatment.